Different Cis-Regulatory Elements Control the Tissue-Specific Contribution of Plastid ω-3 Desaturases to Wounding and Hormone Responses - Luján, María A.; Soria-García, Ángel; Claver, Ana; Lorente, Patricia; Rubio, María C.; Picorel, Rafael; Alfonso, Miguel (Frontiers in Plant Science, 2021)
Trienoic fatty acids are essential constituents of biomembranes and precursors of jasmonates involved in plant defence responses. Two ω-3 desaturases, AtFAD7 and AtFAD8, synthetize trienoic fatty acids in the plastid. Promoter::GUS and mutagenesis analysis was used to identify cis-elements controlling AtFAD7 and AtFAD8 basal expression and their response to hormones or wounding. AtFAD7 promoter GUS activity was much higher than that of AtFAD8 in leaves, with specific AtFAD7 expression in the flower stamen and pistil and root meristem and vasculature. This specific tissue and organ expression of AtFAD7 was controlled by different cis-elements. Thus, promoter deletion and mutagenesis analysis indicated that WRKY proteins were essential for basal expression of AtFAD7 in leaves. Two MYB target sequences present in the AtFAD7 promoter were responsible for its expression in the flower stamen and stigma of the pistil and in the root meristem, and for the AtFAD7 wound-specific response. Two MYB target sequences detected in the distal region of the AtFAD8 gene promoter seemed to negatively control AtFAD8 expression, particularly in true leaves and flowers, suggesting that MYB transcription factors act as repressors of AtFAD8 gene basal expression, modulating the different relative abundance of both plastid ω-3 desaturases at the transcriptional level. Our data showed that the two ABA repression sequences detected in the AtFAD7 promoter were functional, suggesting an ABA-dependent mechanism involved in the different regulation of both ω-3 plastid desaturases. These results reveal the implication of different signaling pathways for the concerted regulation of trienoic fatty acid content in Arabidopsis.